FATHER AND MOTHER ARE SHARE RESPONSIBLE FOR EDUCATION OF THEIR MINOR CHILDREN - Azizov Iqbol Gulyamovich (Journals Park Publishing, 2023)
This article analyzes the topic of the father and mother being equally responsible for the upbringing of their minor children. Educating young people is a sacred duty of every parent to the Motherland. He should approach this duty responsibly. Parents who want to secure their future should spend their time and effort on raising their children who will be great people of tomorrow. The work spent on other areas may be lost, but the work spent on the development of the child will become an inexhaustible treasure. It is no exaggeration to say that the money and time spent on the development of a child is the basis for a prosperous life tomorrow.
Keywords: family, parents, education, duty, responsibility, obligation, right, minor children.